EMERGENCY REMOTE TEACHING IN INDONESIA: A MISSED OPPORTUNITY FOR GREATER LEARNER AUTONOMY - Defianty, Maya; Wilson, Kate (TEFLIN Journal, 2023)
The sudden switch to learning from home during the COVID-19 pandemic impacted teachers across the world. In Indonesia, schools were closed from early March 2020 onwards. This paper presents the findings of a qualitative research project that investigated how Indonesian teachers of English responded to the challenges of Emergency Remote Teaching (ERT) and whether ERT would lead to greater learner autonomy. Ten teachers responded to an invitation to participate in focus groups and individual interviews on Zoom and to contribute examples of their lesson plans from the lockdown period. All teachers found that WhatsApp was the most efficient and effective platform for remote teaching, allowing synchronous and asynchronous sharing of audio, video and text-based materials. Despite the challenges of poor connectivity and lack of face-to-face contact, the teachers were able to continue involving their students actively in integrated, communicative tasks that pushed them to extend their communicative competence. Unexpectedly, however, the move to online teaching did not herald a shift towards greater learner autonomy. The data from this research shows that English language teaching in Indonesia is still firmly teacher-controlled despite the affordances of online learning.